Monitoring oriental fruit moth and codling moth (Lepidoptera: Tortricidae) with combinations of pheromones and kairomones - Knight, Alan L.; Cichon, Liliana; Lago, Jonatan; Fuentes-Contreras, Eduardo; Barros-Parada, Wilson; Hull, L.; Krawczyk, Greg; Zoller, B.; Hansen, Randy; Hilton, R.; Basoalto, Esteban (Wiley, 2019)
Experiments were conducted in North and South America during 2012–2013 to evaluate the use of lure combinations of sex pheromones (PH), host plant volatiles (HPVs) and food baits in traps to capture the oriental fruit moth, Grapholita molesta (Busck), and codling moth, Cydia pomonella (L.), in pome and stone fruit orchards treated with sex pheromones. The combination of the sex pheromone of both species (PH combo lure) significantly increased G. molesta and marginally decreased C. pomonella captures as compared with captures of each species with either of their sex pheromones alone. The addition of a HPV combination lure [(E,Z)‐2,4‐ethyl decadienoate plus (E)‐β‐ocimene] or acetic acid used alone or together did not significantly increase the catch of either species in traps with the PH combo lure. The Ajar trap baited with terpinyl acetate and brown sugar (TAS bait) caught significantly more G. molesta than the delta trap baited with PH combo plus acetic acid in California during 2012. The addition of a PH combo lure to an Ajar trap significantly increased catches of G. molesta compared to the use of the TAS bait or PH combo lure alone in 2013. Female G. molesta were caught in TAS‐baited Ajar traps at similar levels with or without the use of additional lures. Ajar traps baited with the TAS bait alone or with (E)‐β‐ocimene and/or PH combo lures caught significantly fewer C. pomonella than delta traps with sex pheromone alone. Ajar traps with 6.4‐mm screened flaps caught similar numbers of total and female G. molesta as similarly baited open Ajar traps, and with a significant reduction in the catch of non‐targets. Broader testing of HPV and PH combo lures for G. molesta in either delta or screened or open Ajar traps is warranted.